Relationship of the levels of reactive oxygen species in the fertilization medium with the outcome of in vitro fertilization following brief incubation - Niu, Jianing; Chang, Qiurong; Xu, Junting; Li, Jinli; Liu, Wenqiang; Chen, Zhiqin; Jiao, Xianting; Guo, Yi; Teng, Xiaoming (Frontiers in Endocrinology, 2023)
Embryo selection in in vitro fertilization–embryo transfer (IVF-ET) mostly relies on morphological assessment using a conventional microscope or the time-lapse monitoring system, which is not comprehensive. Inappropriate levels of reactive oxygen species (ROS) in the fertilization medium may cause damage to gametes, eventually leading to adverse IVF outcomes. The present study aimed to identify the optimal oxidation–reduction level in the fertilization medium for IVF outcomes by measuring the static oxidation–reduction potential (sORP) using a highly accurate and sensitive MiOXSYS system. A total of 136 patients undergoing IVF following brief incubation were divided equally into 4 groups in this prospective cohort study. The sORP value in the fertilization medium was detected using the MiOXSYS system, and its relationship with IVF outcomes was analyzed. The primary outcome was pregnancy outcomes, including live birth rate (LBR), clinical pregnancy rate (CPR), biochemical pregnancy rate (BPR), and implantation rate (IR). The secondary outcome was embryo quality, including fertilization rate (FR), cleavage rate (CR), available embryo rate (AER), and good-quality embryo rate (GQER). Group II (sORP: 228.7–235.3 mV) showed a higher LBR, CPR, BPR, and IR compared with Group III (sORP: 235.4–242.7 mV), presented as follows: LBR (32.0% for Group II vs 3.6% for Group III, P = 0.033), CPR (32.0% for Group II vs 3.6% for Group III, P = 0.033), BPR (36.0% for Group II vs 3.6% for Group III, P = 0.019), and IR (31.3% for Group II vs 2.7% for Group III, P = 0.003). The FR in Groups I and II had lower significant differences compared with that in Groups III and IV (71.7% and 70.3% for Groups I and II vs 83.5% and 80.4% for Groups III and IV, P = 0.000). The GQER in Group I to Group IV was 32.7%, 37.4%, 26.5%, and 31.7%, respectively (P = 0.056). This study indicated that the sORP value in the fertilization medium might be a potential indicator of embryo quality and pregnancy outcome.